ARCC network checklist for authors: Six things to do when you submit an article for publication - Hewer, F (ARCC, 2015)
The checklist describes six things authors should do to make their publication easier for others to find and use. It was written for built environment and infrastructure researchers whose work is funded by the Engineering and Physical Sciences Research Council (EPSRC). Applying this checklist makes articles eligible for the post-2014 REF, comply with the EPSRC policy framework on research data (1 May 2015), and ensures funders have a record of your research project’s achievements.